“Cut and Paste” Processes in the Search of Bioactive Products: One-Pot, Metal-free O-Radical Scission-Oxidation-Addition of C, N or P-Nucleophiles - Porras, Marina; Hernández, Dácil; González, Concepción C.; Boto, Alicia (Frontiers in Chemistry, 2022)
Hypervalent iodine reagents have been applied in many metal-free, efficient synthesis of natural products and other bioactive compounds. In particular, treatment of alcohols, acetals and acids with hypervalent iodine reagents and iodine results in O-radicals that can undergo a β-scission reaction. Under these oxidative conditions, derivatives of amino acids, peptides or carbohydrates are converted into cationic intermediates, which can subsequently undergo inter- or intramolecular addition of nucleophiles. Most reported papers describe the addition of oxygen nucleophiles, but this review is focused on the addition of carbon, nitrogen and phosphorous nucleophiles. The resulting products (nucleoside and alkaloid analogs, unnatural amino acids, site-selectively modified peptides) are valuable intermediates or analogs of bioactive compounds.